Philosophy and Knowledge in the Tvventy-first Century: Redefining the Role of Universities and Schools (2022)
Philosophy and knowledge are indispensable in the process and practice of education. The essence of education is to train human mind. Education enables one to reason and think critically using mind. Knowledge is essential in the process of education. What kinds of things can be known? How can it be said that a learner knows something? These questions make knowledge one of the most fundamental aspects of philosophy and education. This paper reviews literature to examine what knowledge is and what it ought to be in the 21st century. It employs speculative approach, conceptual analysis and prescriptive research methods in philosophy to expound the creation of knowledge that will be relevant far the 21st century society. The paper has revealed that there are educational initiatives in place that are being taken in the 21st century to set an educational agenda that meets the local and global standards/needs. This implies that universities and schools have an increased role to play in the 21" century including training and recruiting learners, who can, at different levels, demonstrate creativity, critical thinking, communication and collaboration. The paper recommends that knowledge creation must extend to include the physical, mental, emotional and social domains of learning as required in the 21st century.